Quick Response Crisis Communication Strategies Insights from Public Relations PT. KAI DAOP 2 Bandung's Train Accident Response - cintia, Cintia; Susanti, Tantri Aditya; Amanda, Grisha; Nuruzzaman, Muhammad; Lestari, Aghnia Dian (Al-Makki Publisher, 2024)
A crisis can happen to a company that can potentially damage its reputation. But if the crisis can be handled properly, the crisis will not be detrimental to the company. In this study, the author discusses the Daop 2 Bandung Public Relations Crisis Communication Strategy in the case study of the Turangga – CL Bandung Raya Train Accident using a qualitative method with descriptive presentation, while the analysis obtained through interviews with one informant, observation and documentation data. The purpose of this study is to find out the crisis communication steps and efforts taken by Daop 2 Bandung Public Relations in dealing with crisis situations caused by train accidents. The results of the study show that KAI Public Relations has made several efforts to maintain the company's image, namely: First, PT KAI's pre-crisis applies the principle of zero accident by improving employee competence and discipline as well as maintaining facilities and infrastructure. Second, the crisis of PT KAI collaborates with stakeholders, provides solutions, is quick to respond in serving the media by preparing accurate data and fact information. Third, post-crisis improves the image by compensating employees and accident victims and conducting evaluations to improve railway safety and security in the future.